Eurytemora americana Williams, 1906, not Eurytemora affinis (Poppe, 1880), inhabits the Bahía Blanca estuary, Argentina - Hoffmeyer, Monica Susana (2000)
The aim of this report is to clarify the taxonomical identity of the species of Eurytemora (Copepoda, Calanoi- da) present in the Bahía Blanca estuary, Argentina. Observations of taxonomical details were performed and the results led us to conclude that this species is Eurytemora americana Williams, 1906 and not Eurytemora affinis (Poppe, 1880), as pre- viously identified. E. americana is a recent invader in this estuary and could have been accidentally introduced with ballast water of ships